Micro-Macro-Relations in the Kirk-Coleman-Model - Schwenk, Gero; Justus Liebig University Giessen (My University, 2004)
The subject of this work is the analysis of level-transition and emergence problems. Philosophical argument is basically grounded on concepts of object identity and manipulation. It is furthermore extended to criticism of the methodology of bridge-hypotheses as proposed by methodological individualism in the social sciences. In order to provide an actual example, the proposed methodology is implemented: Area of application is the classical Kirk-Coleman-Model, a simulation of interaction behavior in a three-person group. In order to meet the requirements of the proposed methodology of level-transitory explanation the model is modifed and implemented employing the powerful Bayesian-Network formalism.
Keywords: Bayes´sche Netzwerke; Simulation; Mikro-Makro-Gap; Emergenz; Reduktion; Bayesian Networks; Simulation; Micro-Macro-Gap; Emergence; Reduction; ddc:300